Circulating B-type natriuretic peptides in patients with acute coronary syndromes - Jarai, Rudolf; Wojta, Johann; Huber, Kurt (Thrombosis and Haemostasis, 2005)
Fifty percent of patients who experience death or develop heart failure after acute coronary syndromes (ACS) have extremely elevated concentrations of plasma B-type natriuretic peptides. These elevations, however, seem not to reflect permanent ventricular dysfunction or heart failure and are assumed to exist already at the onset of ischemic symptoms. The underlying mechanisms of BNP/Nt-proBNP elevations in patients withACS are still not known at present. Furthermore, the relationship of elevated BNP/Nt-proBNP with mortality but not with atherothrombotic complications of underlying disease makes it difficult to choose optimal therapeutic strategies based on plasma levels of these peptides. The remarkably high short- and long-term mortality rate associated with increases of BNP/Nt-proBNP elevations clearly show the need of further investigation to focus on this high-risk group of patients in order to clarify underlying pathomechanisms and to find optimal therapeutic approaches.
Keywords: B-type natriuretic peptides; acute coronary syndromes